Cirque du Freak. The vampire's assistant [videorecording (DVD)] - Leslie, Ewan; Shuler-Donner, Lauren; Weitz, Paul, 1966-; Helgeland, Brian; Reilly, John C., 1965-; Hutcherson, Josh; Massoglia, Chris; Carlson, Jessica; Cerveris, Michael; Stevenson, Ray, 1964-2023; Fugit, Patrick, 1982-; Watanabe, Ken, 1959-; et al. (Shan, Darren. Saga of Darren Shan., 2010)
Darren is a regular teenage kid. He and his friend Steve find out about a Freak Show coming to town and get tickets. Steve and Darren think that it is all a joke until a vampire named Larten Crepsley comes on stage with a very poisonous spider that he makes do tricks. Steve tells Larten he would like to join him and become an apprentice.